Analisis Bagi Hasil Antara Investor Dan Pengelola Ditinjau Dari Hukum Ekonomi Syariah - Nurasari, Nurasari; Santoso, Rudi (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
Caffe D'jo Seven implements a business practice where the capital owner entrusts the manager to manage the business with the full capital provided. In this cooperation, the profit is divided after the return of capital: 60% for the owner and 40% for the manager. Although the agreement is only verbal, the profit sharing is still carried out fairly, and losses - if not caused by the manager's negligence - are borne by the capital owner. This study focuses on the analysis of the profit sharing system at Caffe D'jo Seven, as well as a review of Islamic economic law related to this practice, in accordance with the principles of Mudharabah. The main objective of the study is to explore the mechanism of cooperation between the owner and manager and to understand the implications of Islamic economic law from the profit sharing practices applied. The research method used is qualitative descriptive, with data collection from interviews, questionnaires, and observations of both parties - the capital owner and the manager. Secondary data was also collected through a review of relevant literature. The results of the study indicate that although the profit sharing practice at Caffe D'jo Seven follows the principles of Mudharabah Muqayyadah, in many cases entrepreneurs do not fully implement this concept, especially in terms of profit sharing and responsibility for losses. This study provides insight into how the profit-sharing system should be run to comply with Islamic economic law.